Hepatitis B virus genotype G and liver fibrosis progression in chronic hepatitis B and human immunodeficiency virus coinfection. Issue 4 (3rd December 2018) - Malagnino, Vincenzo; Bottero, Julie; Miailhes, Patrick; Lascoux‐Combe, Caroline; Girard, Pierre‐Marie; Zoulim, Fabien; Lacombe, Karine; Boyd, Anders
Abstract : Introduction: Infection with hepatitis B virus (HBV) genotype G has been associated with increased liver fibrosis levels compared with other genotypes in cross‐sectional studies, yet its role in fibrosis evolution remains to be established. Methods: In this prospective cohort study, 158 human immunodeficiency virus (HIV)‐HBV coinfected patients had available HBV genotyping at baseline. Liver fibrosis was assessed at baseline and every 6 to 12 months by the FibroTest (BioPredictive, Paris, France). Risk factors for fibrosis regression (F3‐F4 to F0‐F1‐F2) and progression (F0‐F1‐F2 to F3‐F4) between baseline and end of follow‐up were evaluated. Results: Most patients were male (88.6%) with a median age of 39 years. HBV genotype A was more prevalent compared with other HBV genotypes (62.7% vs D = 10.8%, E = 10.8%, and G = 15.8%). Patients were followed up for a median of 83 months (IQR = 37‐97). In the 43 (27.2%) patients with F3‐F4 baseline liver fibrosis, 7 (16.2%) regressed to F0‐F1‐F2 fibrosis at the last follow‐up visit. In the 115 (72.8%) with F0‐F1‐F2 fibrosis at baseline, 19 (16.5%) progressed to F3‐F4 fibrosis at last visit. In multivariable analysis, fibrosis progression was independently associated with older age ( P  <0.005), baseline CD4+ cell count less than 350/mm 3 ( P  <0.01), longer antiretroviral therapy duration ( P  <0.03), and HBV genotype G infection (vs non‐G, P  <0.01). When examining averages over time, the rate of FibroTest increase was faster in genotype G vs non‐G–infected patients with baseline F0‐F1‐F2 fibrosis ( P for interaction = 0.002). Conclusion: In HIV‐HBV coinfected patients, HBV genotype G is an independent risk factor for liver fibrosis progression as determined by noninvasive markers. HBV genotype G–infected patients with low initial liver fibrosis levels may require more careful monitoring.